Grey Area Regulating Amsterdam's Coffeeshops - Jacques, Scott (UCL Press, 2019)
Coffeeshops are the most famous example of Dutch tolerance. But in fact, these cannabis distributors are highly regulated. Coffeeshops are permitted to break the law, but not the rules. On the premises, there cannot be minors, hard drugs or more than 500 grams. Nor can a coffeeshop advertise, cause nuisance or sell over five grams to a person in a day. These rules are enforced by surprise police checks, with violation punishable by closure. In Grey Area, Scott Jacques examines the regulations with a huge stash of data, which he collected during two years of fieldwork in Amsterdam. How do coffeeshop owners and staff obey the rules? How are the rules broken? Why so? To what effect? The stories and statistics show that order in the midst of smoke is key to Dutch drug policy, vaporising the idea that prohibition is better than regulation. Grey Area is a timely contribution in light of the blazing reform to cannabis policy worldwide.